Answer:
1. B. (9, 4)
2. D. (2, -7)
3. C. (20, 30)
4. C. (3/4, -1/5)
Explanation:
1.
Eq.1 3x – 5y = 7 Multiply by -2.
Eq. 2 2x + 3y = 30 Multiply by 3.
Eq. 1 becomes: -6x + 10y = -14
Eq. 2 becomes: 6x + 9y = 90
Add the two new equations to get:
19y = 76
y = 4
Now substitute 4 for y in the first original equation and solve for x.
3x - 5(4) = 7
3x -20 = 7
3x = 27
x = 9
Answer: (9, 4)
2.
2x + 3y = -17 Multiply by -2
5x + 2y = -4 Multiply by 3
-4x - 6y = 34
15x + 6y = -12
Add last two equations.
11x = 22
x = 2
Substitute x = 2 into first original equation and solve for y.
2x + 3y = -17
2(2) + 3y = -17
4 + 3y = -17
3y = -21
y = -7
Answer: D. (2, -7)
3.
x + y = 50 Keep equation as it is.
0.05x + 0.06y = 2.8 Multiply by -20.
x + y = 50
-x - 1.2y = -56
Add last two equations.
-0.2y = -6
y = 30
Substitute y = 30 in first original equation and solve for x.
x + y = 50
x + 30 = 50
x = 20
Answer: C. (20, 30)
4.
8g - 5h = 7 Keep as is.
4g + 10h = 1 Multiply by -2.
8g - 5h = 7
-8g - 20h = -2
Add last two equations.
-25h = 5
h = -1/5
Substitute h = -1/5 into h of first original equation and solve for g.
8g - 5h = 7
8g - 5(-1/5) = 7
8g + 1 = 7
8g = 6
g = 6/8
g = 3/4
Answer: C. (3/4, -1/5)